2019
DOI: 10.5194/acp-19-10801-2019
|View full text |Cite
|
Sign up to set email alerts
|

Severe winter haze days in the Beijing–Tianjin–Hebei region from 1985 to 2017 and the roles of anthropogenic emissions and meteorology

Abstract: Abstract. We applied a global 3-D chemical transport model (GEOS-Chem) to examine the variations in the frequency and intensity in severe winter haze days (SWHDs) in Beijing–Tianjin–Hebei (BTH) from 1985 to 2017 and quantified the roles of changes in anthropogenic emissions and/or meteorological parameters. Observed SWHDs were defined as the days with daily mean PM2.5 concentration exceeding 150 µg m−3, and simulated SWHDs were identified by using the same threshold but with adjustment on the basis of simulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 73 publications
9
70
0
Order By: Relevance
“…Excluding the year 2010 did not affect the change in the trend of the two periods, with a decreased rate of 3.82 d per decade during the 1991-2009 period and an increased rate of 20.76 d per decade during the 2011-2018 period (passing the 95 % t test). In addition, Dang and Liao (2019) confirmed the varying trend of HD NC via simulations of the global 3-D chemical transport (GEOS-Chem) model; using the well-simulated frequency of serious haze days in winter, they also revealed the abovementioned changing trend of HD NC , i.e., decreasing in the early period and increasing in the later period. To further determine the reliability of the post-2010 upward trend of HD NC , we used hourly PM 2.5 concentrations observed at the US embassy in Beijing from 2009 to 2017 and the PM 2.5 concentrations over North China monitored by China National Environmental Monitoring Centre from 2014 to 2018 to count the number of days when the PM 2.5 concentrations were >75 and >100 µg m −3 (Fig.…”
Section: Trend Change In Early Winter Hazesupporting
confidence: 65%
See 2 more Smart Citations
“…Excluding the year 2010 did not affect the change in the trend of the two periods, with a decreased rate of 3.82 d per decade during the 1991-2009 period and an increased rate of 20.76 d per decade during the 2011-2018 period (passing the 95 % t test). In addition, Dang and Liao (2019) confirmed the varying trend of HD NC via simulations of the global 3-D chemical transport (GEOS-Chem) model; using the well-simulated frequency of serious haze days in winter, they also revealed the abovementioned changing trend of HD NC , i.e., decreasing in the early period and increasing in the later period. To further determine the reliability of the post-2010 upward trend of HD NC , we used hourly PM 2.5 concentrations observed at the US embassy in Beijing from 2009 to 2017 and the PM 2.5 concentrations over North China monitored by China National Environmental Monitoring Centre from 2014 to 2018 to count the number of days when the PM 2.5 concentrations were >75 and >100 µg m −3 (Fig.…”
Section: Trend Change In Early Winter Hazesupporting
confidence: 65%
“…The GEOS-Chem model has been widely used. Dang and Liao (2019) used the model to show that the simulated spatial patterns and daily variations of winter PM 2.5 based on GEOS-Chem agree well with the observations from 2013 to 2017, which are the available years with measured PM 2.5 . We selected the year of 2015, as emission reduction just begun to strengthen, and 2017, as this is when the air pollution prevention and management plan for "2 + 26" cities launched (Yin and Zhang, 2020), as two representative years to simulate the actual PM 2.5 concentrations, so as to evaluate the performance of the GEOS-Chem model.…”
Section: Geos-chem Description and Experimental Designmentioning
confidence: 76%
See 1 more Smart Citation
“…The annual mean PM 2.5 concentrations in Beijing and in BTH in 2017 were reduced to 58 µg m -3 and 64 µg m -3 (Ministry of Ecology and Environment of the People's Republic of China, 2018), respectively, both meeting the improvement targets set by the Action Plan. However, analyses of observations showed that the frequency and intensity of wintertime haze events over the NCP have not shown significant decline since 2013 Dang and Liao, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The region of the North China Plain (hereafter referred to as the "NCP", as shown in Fig. 1(b)), including the Beijing-Tianjin-Hebei (BTH) area and the surrounding provinces of Shandong and Henan, has been experiencing severe winter haze pollution events of hourly PM 2.5 concentrations exceeding 150 µg m -3 in recent years (Dang and Liao, 2019), which pose threats to public health (e.g., Chen et al, 2013). These severe wintertime PM 2.5 pollution events are typically associated with the accumulation of PM 2.5 and its precursors under stagnant weather conditions.…”
Section: Introductionmentioning
confidence: 99%